Fístulas dentales en el perro: estudio epidemiológico - Hernández, S.Z. (2007)
An epidemiological study of dental fi stulae was carried out at the Surgical Service of the Veteriary Teaching Hosiptal (FVC - UBA) from 1996 to 2006. The patients affected with dental fistulae represented 1.18% of the total dogs attended. 152 fistulae in 136 dogs were observed, the condition was presented bilaterally in 16 dogs (11.76%). The most fi stulae prevalence was observed in mongrel dogs (58.82%), female (69.85%) between 6 and 12 years old (62.49%). The German Sheperd was the most affected pure breed (8.82%), only five brachycephalic dogs presented fistulae (3.68%). The most affected tooth was the upper fourth premolar (84.21%), followed by the upper fi rst molar (11.84%), upper canine teeth (1.97%) and lower fi rst molar (1.97%). In relation with the upper fourth premolar roots, the distal one was involved in 86 cases (67.18%), the mesiovestibular in 17 (13.28%) and both of them in 25 (19.53%). It is very important to perform an adequate radiological diagnosis in order to determine the tooth (and root) that originates the fistulae, and be able to perform the suitable treatment (exo or endodontic).